Diffraction efficiency adjustment to record high quality color holograms (2015)
In this article, we report the experimental values of required exposure to obtain the maximum diffraction efficiencies in PFG-03C Slavich film on independent recordings and RGB multiplexed recordings -- Also, color adjustments by modifying wavelength channels contribution on reflection diffraction gratings, and color composition changes on Denisyuk holograms observed by using different spectral compositions light sources were studied and presented